Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan pada PT.Tigaraksa Satria Tbk,Jambi - Edo Ramadhan Syah; Riri Mayliza (JURNAL PUNDI, 2021)
This research was conducted to determine and analyze how much influence the Leadership Style, Compensation, and Performance in PT. Tigaraksa Satria TBK Jambi. The instrument used in this study is a statement consisting of several statements about leadership style and compensation for employee performance. This study uses a saturated sample, where the entire research population will be selected as a sample of 48 people. The analysis technique used is multiple regression using SPSS tools. Research Results Based on the tests that have been carried out on leadership style on employee performance, the leadership style variable has a positive and significant effect on employee performance at PT. Tigaraksa Satria TBK Jambi, compensation variable has a positive and significant effect on employee performance.